2019
DOI: 10.1177/1756284819836893
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of fecal microbiota transplantation for the treatment of inflammatory bowel disease

Abstract: Fecal microbiota transplantation (FMT) has changed the treatment landscape of Clostridium difficile infection (CDI). Emerging evidence has shown that FMT can also be an effective and safe treatment strategy in CDI with underlying inflammatory bowel disease (IBD). Recently, randomized controlled trials of FMT in ulcerative colitis support its expanding role in restoring gut homeostasis in this disease. However, heterogeneous study designs leave several questions yet to be answered, including how to best positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 51 publications
(67 reference statements)
0
42
0
Order By: Relevance
“…152 There is some evidence that FMT might be effective for UC. [152][153][154][155][156][157] However, because of the chronic alterations in the microbiome of patients with IBD, repeated FMT might be required. In fact, a subgroup analysis of UC cohort studies demonstrated that patients who received a greater number of FMT infusions were more likely to achieve remission.…”
Section: Microbiota-based Strategies In Patients With Ibdmentioning
confidence: 99%
“…152 There is some evidence that FMT might be effective for UC. [152][153][154][155][156][157] However, because of the chronic alterations in the microbiome of patients with IBD, repeated FMT might be required. In fact, a subgroup analysis of UC cohort studies demonstrated that patients who received a greater number of FMT infusions were more likely to achieve remission.…”
Section: Microbiota-based Strategies In Patients With Ibdmentioning
confidence: 99%
“…Despite these challenges, evidence supports that FMT induces clinical remission in UC, particularly when patients received multiple, lower gastrointestinal infusions 126 . Clinical remission was achieved for 28% of UC patients across four randomized controlled trials 127 . Variable response rates to FMT in UC are likely due to the heterogeneity of the disease.…”
Section: Microbiome-based Ibd Therapiesmentioning
confidence: 99%
“…The administration of antibiotics, such as vancomycin, metronidazole, or fidaxomicin, is typically successful in relieving CDI symptoms. However, the treatment of recurrent infections from C. difficile is a great therapeutic challenge, where the transplantation of gut microbiota seems particularly promising in restoring gut homeostasis [104]. After CDI treatment, the risk of a recurrence within 8 weeks is 15-25% and is further increased up to 60% in patients with multiple recurrences [105].…”
Section: Restoration Of the Gut Microbiota As Therapeutic For CDImentioning
confidence: 99%